PREFERENSI MASYARAKAT DALAM PENGGUNAAN AL-QUR'AN DIGITAL - Afif, Zarkasi; Fadlly, Harits; Akbar, Ali; Syatri, Jonni; Mustopa, Mustopa; Jaeni, Ahmad; Hakim, Abdul; Arifin, Zainal; Martiningsih, Dwi; Irwan, Irwan; Musadad, Muhammad (Lajnah Pentashihan Mushaf Al-Qur'an, 2018)
In the end of August 2016, the Ministry of Religious Affairs, in this case the Committee of the Correction of Qur'anic Writing (Lajnah Pentashihan Mushaf Al-Qur'an) launched a digital Qur'an product called Qur'an Kemenag. At present there are only more than 25 thousand active users. This research wants to find out the factors that influence people's preferences in the use of Qur'an Kemenag's application. This study uses a mixed method, namely qualitative and quantitative. The population of this study is the muslim community of smartphone owners and users of the digital Qur'an. The selection of respondents was done by purposive sampling, conducted in 14 cities in Indonesia with a total of 50 respondents per city, and 3 informants for in-depth interviews. This research shows that Qur'an Kemenag is not widely used by muslim communities in Indonesia. They use the digital Al-Qur'an application developed by other parties more than that being developed by Ministry of Religious Affairs. Factor that influences people's preferences for using an Al-Qur'an digital application are features and complete content. In addition to that, the facilities provided are not only the Qur'an, but also multifunctional needs.